The Factors' Influence on Employee Performance of Small Companies in Shandong - Qi, Weijie; Run, Pharatt (Value Added : Majalah Ekonomi dan Bisnis, 2024)
This research investigated the factors influencing employee performance in Shandong small companies. The study explores the influence of demographic factors, including gender, age, education level, monthly income, nature of employment, work experience, and number of employees' influence on employee performance. Additionally, it examines the influence of organizational culture, encompassing Clan, Adhocracy, Market, and Hierarchy cultures on employee performance. This study, based on a survey of 400 employees in small companies in Shandong, utilized a questionnaire as the primary data collection tool. The statistics used to analyze the data were descriptive statistics, including Frequency, Percentage, Mean, and Standard Deviation, and inferential statistics, including Independent Samples t-test, One-way ANOVA, LSD, and Multiple Linear Regression at a significance level of 0.05. The results found that most of the respondents were male, 25-34 years old, with an education level of bachelor, Full-time worker and monthly income of less than 5,000 CNY, work experience of less than 1 year, and Number of employees is 1-10 members. The first hypotheses were tested, and the results found that the differences in gender, age, education level, monthly income, work experience, and Number of employees significantly influenced employee performance. The results of the second hypothesis tested showed that adhocracy, market, clan, and hierarchy cultures significantly influenced employee performance.